Planarian Mucus: A Novel Source of Pleiotropic Cytotoxic and Cytostatic Agents against Cancer Cells - Gaetana Gambino; Eleonora Da Pozzo; Alessandra Salvetti; Leonardo Rossi (Biomolecules)
Biological evolution has generated a vast array of natural compounds produced by organisms across all domains. Among these, secondary metabolites, selected to enhance an organism’s competitiveness in its natural environment, make them a reservoir for discovering new compounds with cytotoxic activity, potentially useful as novel anticancer agents. Slime secretions, the first barrier between epithelial surfaces and the surrounding environment, frequently contain cytotoxic molecules to limit the growth of parasitic organisms. Planarians, freshwater Triclads, continuously secrete a viscous mucus with multiple physiological functions. The chemical composition of planarian mucus has been only partially elucidated, and there are no studies reporting its cytotoxic or cytostatic effects. In this study, we developed a protocol for collecting mucus from Dugesia japonica specimens and we demonstrated that it inhibits the growth of cancer cells by activating cytostatic and ROS-dependent cytotoxic mechanisms inducing lipid droplet accumulation and mitochondrial membrane reorganization. Although further research is needed to identify the specific chemicals responsible for the anticancer activity of planarian mucus, this work opens up numerous research avenues aimed at better understanding the mechanisms of action of this product for potential therapeutic applications.